2019
DOI: 10.21153/thl2019volno0art1033
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care in Humanitarian Crises

Abstract: Palliative care and humanitarian action share fundamental goals to relieve suffering and uphold dignity; and both hold an ethical root in the recognition of our common suffering in illness and dying, our compassionate action in response to suffering, and our common humanity. The parallels in goals and ethos should make universal application of palliative care in humanitarian crises a norm, but in humanitarian practice today this is not the case. There is growing consciousness of the imperative to integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Some researchers have suggested that the urgency of COVID-19 may be a catalyst for new ways of easing suffering within global health agendas, 7 and for strengthening a human rights approach to death and dying. 8 One of the key challenges to providing quality palliative care during COVID-19 has been the sense of separation experienced and felt by patients and their families, as has been shown in previous pandemics. 4 How might we better enable forms of closeness, connection and intimacy for those moving towards the end of life, their loved ones and their clinicians?…”
mentioning
confidence: 99%
“…Some researchers have suggested that the urgency of COVID-19 may be a catalyst for new ways of easing suffering within global health agendas, 7 and for strengthening a human rights approach to death and dying. 8 One of the key challenges to providing quality palliative care during COVID-19 has been the sense of separation experienced and felt by patients and their families, as has been shown in previous pandemics. 4 How might we better enable forms of closeness, connection and intimacy for those moving towards the end of life, their loved ones and their clinicians?…”
mentioning
confidence: 99%
“…COVID-19 makes stark the importance of palliative care delivery alongside lifesaving interventions, but the degree to which these guidelines and others responding to infectious disease outbreaks have heeded the WHO guidelines and integrated palliative care is not yet known. 16 , 18 This review aims to answer the question: to what extent is palliative care included in global guidelines that have been developed to support healthcare systems and providers to respond to infectious disease outbreaks?…”
Section: Introductionmentioning
confidence: 99%